Strategic Communication in the Digital Age: Examining Linguistic Mechanisms and Media Influence on Public Consciousness Amidst Political Tensions - Koliechkin, Valentyn; et al. (European Journal of Social Science Education and Research, 2026)
At the current stage of social development, political conflicts with ideological underpinnings increasingly attract public attention. In such circumstances, public opinion should remain as free as possible from manipulative political influences, as this contributes to the consolidation and sustainable development of civil society in Ukraine. The mass media and political discourse play a decisive role in shaping public awareness and interpretations of political conflicts. The aim of this study is to provide an in-depth analysis of communication and speech phenomena in contemporary political conflicts and to assess their impact on social dynamics, particularly on the level of public trust in the media. The research is based on a qualitative analysis of political discourse and a comparative examination of the most significant political speeches delivered over the past fifty years. The study also evaluates current media practices and the role of social networks in political communication. Key trends in the representation of political conflicts have been identified, including the simplification of public political speeches, minimization of content, increased reliance on emotional narratives, and intensified influence on the electorate through the presentation of promising strategies. The findings reveal a gradual adaptation of political rhetoric to audience perception capacities. The growing importance of social networks as tools for political mobilization, voter segmentation, and public engagement has been established. Political conflicts function as catalysts of socio-economic dynamics, while contemporary communication strategies significantly influence public trust, political participation, and the development of civil society.